Social Media and Lifestyle Shape Student Purchasing Patterns - Erma Hotnijar Siregar; Marliyah Marliyah; Nursantri Yanti (Academia Open, 2025)
General Background: Rising access to information and digital platforms has transformed consumption habits among youth, particularly students. Specific Background: Overseas students often face unique financial and social adjustments, making them susceptible to excessive spending. Knowledge Gap: While prior studies have discussed general student consumption, few have focused on overseas students and the role of peer influence, lifestyle, and social media combined. Aims: This study investigates the relationship between social media use, peer relationships, and lifestyle with the consumptive behavior of overseas students at UIN Sumatera Utara. Results: Using a quantitative approach and data from 75 respondents, the findings show that social media and lifestyle are positively and significantly associated with consumptive behavior, while peer influence is not statistically significant. Novelty: This study contributes by centering on migrant students in a developing country context, highlighting that lifestyle choices and media exposure override peer pressure in shaping spending habits. Implications: These results suggest that interventions aiming to reduce excessive consumption among overseas students should prioritize media literacy and financial awareness over peer-group regulation.Highlights: 1. Lifestyle is the strongest predictor of excessive student spending. 2. Peer influence does not significantly drive consumptive behavior. 3. Social media exposure correlates with increased purchase frequency. Keywords: social media, lifestyle, student behavior, consumption, overseas students